Novel Ways to Determine Kinesin-1's Run Length and Randomness Using Fluorescence Microscopy - Verbrugge, Sander (The Biophysical Society, 2009)
The molecular motor protein Kinesin-1 drives intracellular transport of vesicles, by binding to microtubules and making hundreds of consecutive 8-nm steps along them. Three important parameters define the motility of such a linear motor: velocity, run length (the average distance traveled), and the randomness (a measure of the stochasticity of stepping). We used total internal reflection fluorescence microscopy to measure these parameters under conditions without external load acting on the motor. First, we tracked the motility of single motor proteins at different adenosine triphosphate (ATP) concentrations and determined both velocity and (for the first time, to our knowledge, by using single-molecule fluorescence assays) randomness. We show that the rate of Kinesin-1 at zero load is limited by two or more exponentially distributed processes at high ATP concentrations, but that an additional, ATP-dependent process becomes the sole rate-limiting process at low ATP concentrations. Next, we measured the density profile of moving Kinesin-1 along a microtubule. This allowed us to determine the average run length in a new way, without the need to resolve single-molecules and to correct for photobleaching. At saturating ATP concentration, we measured a run length of 1070 ± 30 nm. This value did not significantly change for different ATP concentrations.